Ecce femina – podróż do źródła kobiecości. Wokół krwi menstruacyjnej we współczesnej literaturze polskiej na podstawie wybranych przykładów – Izabeli Filipiak i Olgi Tokarczuk - Andrea Fernando De Carlo (Postscriptum Polonistyczne)
The article analyses myths concerning menstruation in Izabela Filipiak’s and Olga Tokarczuk’s creative works. The writers refer to female physiology in order to abolish the taboo on the female body and its excretions and to create mythology free from the male universe. Menstruation is considered a taboo subject even at the beginning of the 21st century and this physiological aspect of feminity is connected with an attempt to respect the differences between the sexes. One can observe not so much an attempt to destroy the rules of patriarchal culture, but a need to recreate the Western imagination, which is able to renew social and symbolic order and create new female mythology, which enables women to identify with their own needs, feelings, physical, sexual and erotic experiences.